‘Perception matters’: New insights into the subjective dimension of resilience in the context of humanitarian and food security crises - Béné, Christophe; Frankenberger, Timothy; Griffin, Tiffany; Langworthy, Mark; Mueller, Monica; Martin, Stephanie (SAGE Publications, 2019)
In the emerging literature on resilience in relation to food security, a growing number of studies stress the need to expand our analysis beyond conventional socio-economic factors such as assets or social capital, and to consider less tangible elements such as risk perception, self-efficacy or aspiration. Drawing on the recent literature and the authors’ own experience, a conceptual framework of subjective resilience is proposed. The framework helps locating the subjective element of resilience within the wider resilience conceptualization as currently developed in the literature on food security and to clarify how it links to the more tangible elements of that conceptualization. Empirical data are then used to test the framework. The analysis demonstrates the relevance of the concept of subjective resilience and the central role that psychosocial factors and individual perceptions play in people’s construct of resilience in the context of humanitarian and food security crises. The article concludes with a discussion of the implications of those findings.